2012
DOI: 10.1186/1743-422x-9-83
|View full text |Cite
|
Sign up to set email alerts
|

Porcine reproductive and respiratory syndrome virus nonstructural protein 2 contributes to NF-κB activation

Abstract: BackgroundNuclear factor-kappaB (NF-κB) is an inducible transcription factor that plays a key role in inflammation and immune responses, as well as in the regulation of cell proliferation and survival. Previous studies by our group and others have demonstrated that porcine reproductive and respiratory syndrome virus (PRRSV) infection could activate NF-κB in MARC-145 cells and alveolar macrophages. The nucleocapsid (N) protein was identified as an NF-κB activator among the structural proteins encoded by PRRSV; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 45 publications
(56 reference statements)
2
35
1
Order By: Relevance
“…Examples of such viral proteins include the PRRSV structural protein N and the non-structural protein 2 (NSP2) (Fang et al, 2012;Fu et al, 2012;Luo et al, 2008), herpes simplex virus glycoproteins gH/gL and gB (Leoni et al, 2012), Epstein-Barr virus latent membrane protein 1 (Smirnova et al, 2011), HIV envelope glycoprotein gp120 (Bren et al, 2009), SARS-CoV proteins S and N (Dosch et al, 2009;Liao et al, 2005), and hepatitis C virus protein NSP2 (Oem et al, 2008). Virion envelope proteins could initiate NF-kB activation by binding to cellular surface receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such viral proteins include the PRRSV structural protein N and the non-structural protein 2 (NSP2) (Fang et al, 2012;Fu et al, 2012;Luo et al, 2008), herpes simplex virus glycoproteins gH/gL and gB (Leoni et al, 2012), Epstein-Barr virus latent membrane protein 1 (Smirnova et al, 2011), HIV envelope glycoprotein gp120 (Bren et al, 2009), SARS-CoV proteins S and N (Dosch et al, 2009;Liao et al, 2005), and hepatitis C virus protein NSP2 (Oem et al, 2008). Virion envelope proteins could initiate NF-kB activation by binding to cellular surface receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Procedure for confocal fluorescence microscopy was described previously (Fang et al, 2012). Briefly, HeLa cells were seeded on glass coverslips (NEST Biotechnology) that had been placed in 24-well plates until cultures were 70-80% confluent.…”
Section: Confocal Fluorescence Microscopymentioning
confidence: 99%
“…Previous studies have demonstrated that nsp2 uses its DUB activity to inhibit NF-κB activation by suppressing the polyubiquitination process of IκBα and nuclear translocation of NF-κB [29], and to inhibit type I IFN production by blocking the ubiquitination of RIG-I [25]. Among the identified cellular proteins interacting with nsp2, some of them are involved in innate immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Gene fragments of a series of PRRSV WUH3 nonstructural and structural genes were cloned into the pCAGGS-HA vector in-frame as previously described [29]. Gene fragments encoding PRRSV nsp2 and N proteins were inserted into the pCAGGS-Flag vector to construct pCAGGS-Flag nsp2 and pCAGGS-Flag-N, respectively.…”
Section: Antibodies Reagents and Plasmidsmentioning
confidence: 99%